(untitled) (Scientific journal of the Fergana State University, 2023)
This theoretical study investigates the transport of natural solar radiation in atmospheric layers, considering the Rayleigh scattering on air molecules. The article focuses on calculating the spectral and angular distributions of diffusely reflected, transmitted, and non-scattered solar radiation emerging from the atmospheric layers. The intensity calculations for diffuse radiation utilize Chandrasekhar’s -matrix theory and employ a factorization method. The obtained results offer valuable insights into the behavior of solar radiation in terms of its spectral and angular characteristics, considering the scattering effects induced by air molecules.